Acute oral toxicity and risks of four classes of systemic insecticide to the Common Eastern Bumblebee (Bombus impatiens). (May 2022) - Mundy-Heisz, Kayla A.; Prosser, Ryan S.; Raine, Nigel E.
Abstract: The Common Eastern Bumblebee ( Bombus impatiens ) is native to North America with an expanding range across Eastern Canada and the USA. This species is commercially produced primarily for greenhouse crop pollination and is a common and abundant component of the wild bumblebee fauna in agricultural, suburban and urban landscapes. However, there is a dearth of pesticide toxicity information about North American bumblebees. The present study determined the acute oral lethal toxicity (48-h LD50) of: the butenolide, flupyradifurone (>1.7 μg/bee); the diamide, cyantraniliprole (>0.54 μg/bee); the neonicotinoid, thiamethoxam (0.0012 μg/bee); and the sulfoximine, sulfoxaflor (0.0177 μg/bee). Compared with published honey bee ( Apis mellifera ) LD50 values, the present study shows that sulfoxaflor and thiamethoxam are 8.3× and 3.3× more acutely toxic to B. impatiens, whereas flupyradifurone is more acutely toxic to A. mellifera . The current rule of thumb for toxicity extrapolation beyond the honey bee as a model species, termed 10× safety factor, may be sufficient for bumblebee acute oral toxicity. A comparison of five risk assessment equations suggested that the Standard Risk Approach (SRA) and Fixed Dose Risk Approach (FDRA) provide more nuanced levels of risk evaluation compared to the Exposure Toxicity Ratio (ETR), Hazard Quotient (HQ), and Risk Quotient (RQ), primarily because the SRA and FDRA take into account real world variability in pollen and nectar pesticide residues and the chances that bees may be exposed to them. Graphical abstract: Image 1 Highlights: Systemic insecticides pose a risk to non-target invertebrates worldwide Bumblebee data are not required in current pesticide regulatory testing Acute oral lethal toxicity trials were completed for 4 systemic insecticide classes Bombus impatiens is more sensitive than Apis mellifera to two insecticides Pesticide regulatory equations should be applied to bumblebees